FAKTOR YANG BERHUBUNGAN DENGAN KEKAMBUHAN PENDERITA HIPERTENSI DI DESA SUMBERTEBU KABUPATEN MOJOKERTO - Dwiharini Puspitaningsih; Mesias Manit (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Things that trigger Hypertension were classified into two; cannot be modified factors, and can be modified factors. This study armed to investigate the factors that triggered the recurrence of hypertension in the patients at Sumbertebu village, Mojokerto. A cross-sectional research design was used to carry on this study. The respondents featured were 35 hypertension patients at Sumbertebu village, Mojokerto. Simple random sampling was used to determine the sample of the population. An interview based on FFQ and PSQI questionnaires was done to collect the data. The data was then processed and analyzed using the rank spearman test. The result suggested that, though there is no relationship between gender and the recurrence of the disease, the dietary and sleeping habits of the patients showed strong relation to the disease’s recurrence with a p-value of 0,283 > α 0,05 for gender, p-value 0,005 < α 0,05 for dietary habit, and p-value 0,005 < α 0,05 for sleeping habit. Periodical counseling and special attention by public health services were needed to approach the complexity of the factors that triggered the disease recurrence. A healthy diet was also required by the patients to generally reduce cardiovascular issues that will trigger Hypertension.